Chandra X-ray constraints on the candidate Ca-rich gap transient SN 2016hnk - Sell PH; Arur K; Maccarone TJ; Kotak R; Knigge C; Sand DJ; Valenti S (OXFORD UNIV PRESS, 2025)
We present a Chandra observation of SN 2016hnk, a candidate Ca-rich gap transient. This observation was specifically designed to test whether or not this transient was the result of the tidal detonation of a white dwarf by an intermediate-mass black hole. Since we detect no X-ray emission 28 d after the discovery of the transient, as predicted from fall-back accretion, we rule out this model. Our upper limit of similar to 10M(circle dot) does not allow us to rule out a neutron star or stellar-mass black hole detonator due limits on the sensitivity of Chandra to soft X-rays and unconstrained variables tied to the structure of super-Eddington accretion discs. Together with other Chandra and multiwavelength observations, our analysis strongly argues against the intermediate-mass black hole tidal detonation scenario for Ca-rich gap transients more generally.